The gradual release of responsibility in literacy research and practice - McVee, Mary; Ortlieb, Evan; Reichenberg, Jennifer; Pearson, P. David (Emerald Publishing Limited, 2019)
Educators are always in search of approaches that promote student development and academic achievement. Engaging learners in purposeful instruction in skills and strategies is a cornerstone in every classroom. The gradual release of responsibility (GRR) model requires the responsibility of learning to shift from being teacher-centric towards students gradually assuming responsibility as independent learners. In the last 35 years, the gradual release of responsibility model of instruction has become synonymous with some of the most effective approaches to teach both skills and content to students of all ages. Evidence-based practices have been documented across the globe not only in literacy but also in most disciplines across the curriculum. While the GRR model is a well-established theory, its implementations have not been researched. This edited volume discusses how the GRR model evolved and has been applied, how it benefits learners and teachers, and how it can be utilised for years to come. By looking not only at the gradual release of responsibility model from a theoretical standpoint but also the research and practice of this approach, this book will prove invaluable for educational leaders and researchers alike.
Includes index.
Keywords: Literacy.; Education.; Education -- Teaching Methods & Materials / Reading & Phonics.; Reading skills.; elektronické knihy; electronic books